The Changes of Family Food Patterns in Two Generations in Padang Genting Village, Batubara Regency (In terms role of women as housewives) - Maswita (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
Changes in family dietary habitary patterns are necessary, although some families persist in generations of family dietary habits. Dietary habit is related to the physical needs of healthy and sustainable living. Some areas in Indonesia, family eating patterns tend to be oriented to family habits from generation to generation. This study aims to analyze the factors that influence housewives in the second generation in compiling their family's dietary habit in the coastal area of the Malacca Strait. This study was conducted in Padang Genting Village, Batubara Regency, North Sumatra. The method used in this study is the ethnographic method with participant observation techniques and in-depth interviews with selected respondents based on the snowball technique and direct observation in the research area. The results of this study concluded that the experience of housewives with their parents, formal education and experience in PKK (Family Welfare Development) in villages and sub-districts also became the basis for women housewives to formulate their family's dietary habitary habit.